C.E. Credit. Bitemark Analysis: The Legal vs Scientific Battle for Justice - Mary A. Bush; Raymond G. Miller; Peter J. Bush (Taylor & Francis Group, 2023)
ABSTRACTThe forensic odontology discipline of bitemark analysis has been under scrutiny for a number of years. The significant issues associated with the practice were outlined in the 2009 National Academy of Sciences Report, the 2016 Texas Forensic Science Commission report, the 2018 President's Commission on Science and Technology, and most recently in a 2022 draft report released by the National Institute of Standards and Technology. Current scientific study does not support the underlying premises of bitemark analysis; that the human dentition is unique and that the unique features transfer to human skin. As such, a number of wrongful convictions have resulted. Some of those convicted have spent over thirty years behind bars for a crime they did not commit, while others were on death row. This review article examines the emergence of bitemark analysis to the legal system, the research work accomplished by the authors of this review, how the legal, forensic odontology, and scientific communities have responded, and the possible path forward.Continuing Education Credit Available: The practice worksheet is available as supplemental material for this article: https://doi.org/10.1080/19424396.2023.2191391.A CDA Continuing Education quiz is online for this article: https://www.cdapresents360.com/learn/catalog/view/20.